2016
DOI: 10.1212/wnl.0000000000002351
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of plasma urate and risk of Parkinson disease in men and women

Abstract: Objective: To examine whether higher plasma urate concentrations are associated with a lower risk of developing Parkinson disease (PD) and whether there is a sex difference in the potential urate-PD relationship. Methods:We conducted a nested case-control study based on 90,214 participants of 3 ongoing US cohorts. We identified 388 new PD cases (202 men and 186 women) since blood collection, which were then matched to 1,267 controls. PD cases were confirmed by medical record review. Conditional logistic regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
96
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 119 publications
(107 citation statements)
references
References 41 publications
6
96
0
Order By: Relevance
“…A sex-difference protective effect of UA on nervous system disease (such as Parkinson disease) had also been reported2627. For example, a recent nested case-control study based on 3 ongoing US cohorts suggested that men, but not women, with higher urate concentrations had a lower future risk of developing Parkinson disease26. The biological mechanisms underlying such sex specificity remain unclear.…”
Section: Discussionmentioning
confidence: 98%
“…A sex-difference protective effect of UA on nervous system disease (such as Parkinson disease) had also been reported2627. For example, a recent nested case-control study based on 3 ongoing US cohorts suggested that men, but not women, with higher urate concentrations had a lower future risk of developing Parkinson disease26. The biological mechanisms underlying such sex specificity remain unclear.…”
Section: Discussionmentioning
confidence: 98%
“…A meta-analysis of three prospective cohort studies and a nested case-control study of three US cohorts obtained a pooled RR of 0.63 (95% CI: 0.42-0.95) in men and 0.89 (95% CI: 0.57-1.40) in women comparing the two extreme quartiles of urate. 60 Higher urate concentrations were found to be protective against PD risk in men, but not in women. 60 Similar findings were obtained in an earlier meta-analysis of four cohort studies performed in the Netherlands and the USA, and two nested case-control studies performed in the USA (RR 0.67, 95% CI: 0.50-0.91); with further subgroup analysis showing protective effects of serum urate in men, but not in women.…”
Section: Urate (Uric Acid)mentioning
confidence: 96%
“…60 Higher urate concentrations were found to be protective against PD risk in men, but not in women. 60 Similar findings were obtained in an earlier meta-analysis of four cohort studies performed in the Netherlands and the USA, and two nested case-control studies performed in the USA (RR 0.67, 95% CI: 0.50-0.91); with further subgroup analysis showing protective effects of serum urate in men, but not in women. 61 Gout is a metabolic disorder that tends to occur in individuals with higher levels of serum uric acid, although other risk factors are also implicated.…”
Section: Urate (Uric Acid)mentioning
confidence: 96%
See 1 more Smart Citation
“…To examine the robustness of the observed results, we conducted a sensitivity analysis by excluding individuals with hyperuricemia (1462 in men and 175 in women) because urate concentration is strongly associated with alcohol consumption and PD status 23, 24. For the same reason, we conducted another sensitivity analysis using the alternative cut‐off point (range 0–70, >7) for determining pRBD based on seven subgroup behavioral factors of RBDQ‐HK, including sleep talking, shouting, limb movements, and sleep‐related injuries.…”
Section: Methodsmentioning
confidence: 99%